2021
DOI: 10.47371/mycosci.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic revision of the Japanese <i>Tricholoma ustale</i> and closely related species based on molecular phylogenetic and morphological data

Abstract: Kakishimeji" identified as Tricholoma ustale and belonging to Tricholoma sect. Genuina is a common poisonous mushroom in Japan. Kakishimeji contains the toxic compound ustalic acid and causes digestive trouble. However, this fungus is consumed in some regions of Japan without any digestive issues. We clarified the probable species complex of Kakishimeji based on a phylogenetic analysis. We collected 89 basidioma specimens of Kakishimeji and related species from various forest sites in Japan and conducted phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Rigida), Terrea, Atrosquamosa, and Genuina [4,7,17]. Tricholidic acid (5) was previously isolated only once, namely, from a Tricholoma species collected in Japan [31], which is probably identifiable as T. albobrunneum [11]; instead, tricholidic acids B (6) and C (7) are novel triterpenoids, isolated for the first time from T. ustaloides in this study. Interestingly, from a chemotaxonomic point of view, both T. albobrunneum and T. ustaloides belong to the section Genuina of Tricholomas [4,7].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Rigida), Terrea, Atrosquamosa, and Genuina [4,7,17]. Tricholidic acid (5) was previously isolated only once, namely, from a Tricholoma species collected in Japan [31], which is probably identifiable as T. albobrunneum [11]; instead, tricholidic acids B (6) and C (7) are novel triterpenoids, isolated for the first time from T. ustaloides in this study. Interestingly, from a chemotaxonomic point of view, both T. albobrunneum and T. ustaloides belong to the section Genuina of Tricholomas [4,7].…”
Section: Discussionmentioning
confidence: 73%
“…The taxonomy and phylogeny of the genus Tricholoma have been based, up to recent times, mainly on fungal morphological characters; however, the use of molecular methods based on nuc rDNA internal transcribed spacer ITS1-5.8S-ITS2 (ITS) sequences is becoming more and more important to analyze the diversity and distribution of several species [7][8][9]. Thus, phylogenetic analyses using nuclear and mitochondrial gene sequences have often proved that mushrooms collected with the same name in different places of the same country/continent [10,11] or in distant continents [8,10] must instead be placed in distinct clades/subclades or even different taxa. For example, Tricholoma pardinum (Pers.)…”
Section: Introductionmentioning
confidence: 99%
“… * N: nucleus; M: mitochondrion 1 Gardes & Bruns (1993) ; 2 White et al (1990) ; 3 Anderson & Stasovski (1992) ; 4 Henrion et al (1992) ; 5 Aoki et al (2021) ; 6 This study; 7 Kretzer & Bruns (1999) ; 8 Binder & Hibbett (2003; ); 9 Babasaki et al (2007) . …”
Section: Methodsmentioning
confidence: 87%
“…(syn. T. batschii Gulden) collected in Germany [21]; and acetyl trichaurantin (11), which was isolated from T. aurantium [21].…”
Section: Trichoaurantianolides and Tricholomalidesmentioning
confidence: 99%
“…The use of molecular methods based on nuclear rDNA internal transcribed spacer ITS1-5.8S-ITS2 (ITS) sequences is becoming more and more important in phylogenetic studies of higher mushrooms [7][8][9], accompanying or even substituting the traditional studies of fungal morphological characters. Thus, it has often been demonstrated that mushrooms growing in different habitats/countries but classified as the same species based on morphological characters, must instead be placed in distinct clades/subclades or even different taxa [8,10,11]. In this context, the distinct chemical contents determined through phytochemical analysis have often confirmed the possible existence of different varieties or taxa [12].…”
Section: Introductionmentioning
confidence: 99%